Health-related Quality of Life in Women with Polycystic Ovary Syndrome - Belén Carazo Hernández; Olivia Lafalla Bernad; Raquel García Simón; Elena Gascón Mas; Esther Moreno Romea; Beatriz Rojas Pérez-Ezquerra (Medisur)
Polycystic ovary syndrome is the most frequent endocrine and metabolic disorder in women of reproductive age. Its characteristic signs and symptoms are menstrual irregularities, amenorrhea, acne, hirsutism, obesity and infertility. Polycystic ovary syndrome has major effects on long-term health, which can lead to psychological morbidity and decreased quality of life. This paper reviews the current literature on polycystic ovary syndrome and health-related quality of life; in addition, it assesses how some clinical manifestations of polycystic ovary syndrome affect the quality of life of women who suffer this disorder.